Embodying the Goddess: The ‘Parvaitin’ in Chaṭha Pūjā - Yadav, Akanksha (Religions of South Asia, 2025)
This study explores the phenomenon of deity embodiment during the Chaṭha festival, focusing on the transformative religious encounters of the female primary worshippers—the parvaitins. The parvaitin transcends human-divine boundaries through her ritual mastery, ritualization and body techniques, and embodies the goddess Chaṭhī Māī. Through ethnographic fieldwork conducted in Varanasi, Patna, Munger and Sahibganj during the years 2021-23, the study delves into the ritual practices, bodily techniques and experiences of the parvaitin. It argues that ritual knowledge, competence and body techniques enable the parvaitin to express and experience the deity, creating a vessel for her to manifest. The study elucidates the negotiation, transformation and agency that occur through the rituals, shedding light on how individuals encounter and manifest the divine. Furthermore, it highlights the consequences and effects of these interactions, providing insights into the multifaceted nature of religious experiences within specific cultural and ritual contexts. This research contributes to a deeper understanding of deity embodiment and its implications within religious practices through participant observation, qualitative interviews and analysis of data obtained.